장안사 대웅전 보존 수리공사와 1930년대 금강산 개발 - 근대기 건축문화유산 보존과 관광지 개발의 영향관계 연구 - 서효원; Seo, Hyowon (건축역사연구 : 한국건축역사학회논문집, 2020)
The purpose of this study was to analyze the correlation between conservation activities and the development of tourism in the modern period in the Korean peninsula. The main building of Jangansa Temple, located in Mt. Geumgang, was repaired in the 1930s. During the repairs, the Japanese General-Government actively engaged in the development of Mt. Geumgang and raised funds for the operation of the Korean Peninsula through tourism revenue. The repair work was carried out under the influence of the Mt. Geumgang development project. And its influence is revealed by reviewing official documents recording repair work. This study tried to clarify the relationship between development and repair work through official documents.